2018
DOI: 10.1002/cam4.1216
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms forecasting long‐term overall and cancer‐specific survival of patients with oral squamous cell carcinoma

Abstract: Our aim was to establish a “nomogram” model to forecast the overall survival (OS) and cancer‐specific survival (CSS) of oral squamous cell carcinoma (OSCC) patients. The clinicopathological data for the 10,533 OSCC patients were collected from the Surveillance, Epidemiology and End Results (SEER) database. We used a credible random split‐sample method to divide 10,533 patients into two cohorts: 7046 patients in the modeling cohort and 3487 patients in the external validation cohort (split‐ratio = 2:1). The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…The C‐indexes for the 3‐, 5‐, and 8‐year OS and CSS rates were 0.748 and 0.783, respectively, in the internal validation, and 0.723 and 0.799 in the external validation. All of these C‐indexes exceed 0.7, and there was excellent coherence between the calibration curves and the 45‐degree ideal lines (Figure ) . The plots resembling 45‐degree lines indicate that the nomogram predictions were well calibrated both in the training and verification cohorts (Figures and ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The C‐indexes for the 3‐, 5‐, and 8‐year OS and CSS rates were 0.748 and 0.783, respectively, in the internal validation, and 0.723 and 0.799 in the external validation. All of these C‐indexes exceed 0.7, and there was excellent coherence between the calibration curves and the 45‐degree ideal lines (Figure ) . The plots resembling 45‐degree lines indicate that the nomogram predictions were well calibrated both in the training and verification cohorts (Figures and ).…”
Section: Discussionmentioning
confidence: 69%
“…Calibration plotting was used to evaluate the agreement between the actual outcome and the predicted probability. There were two lines in the calibration plots: one was the data line and the other was a 45‐degree reference line; the discrepancy between these two lines reflects the accuracy of a nomogram …”
Section: Methodsmentioning
confidence: 99%
“…Our nomogram indicates that pathological grade is the most important factor, while age is the second most important one [15,16], and there is no signi cant difference between grades I and II. Multivariate analyses indicated that older age was an independent risk variable, with older patients having a lower survival rate [9,17,18]. Meanwhile, a higher AJCC stage was associated with worse survival [9].…”
Section: Discussionmentioning
confidence: 94%
“…We found that age, AJCC stage, N stage, M stage, pathological grade, and surgical status were important risk factors for survival. The accuracy of survival prediction may decrease if these important prognostic parameters are ignored [9].…”
Section: Introductionmentioning
confidence: 99%
“…The level of agreement for the second phase was 88% with a kappa of 0.77. A total of 44 studies remained for the final analysis . The list of excluded papers with the reasons for exclusion can be found in the Supporting Information S3.…”
Section: Methodsmentioning
confidence: 99%